"What do coaches do" and "how do they relate": Their effects on athletes' psychological needs and functioning. Issue 2 (18th December 2012) - Felton, L.; Jowett, S.
<x xml:space="preserve">Abstract</x> Grounded in self‐determination theory, this study aimed to examine the links of the social environment, as defined by coach interpersonal behaviors and coach–athlete relationships, with athletes' psychological need satisfaction and indexes of well‐being. Athletes (N = 300) completed a multi‐section questionnaire assessing the study variables. Bootstrap mediation analysis highlighted significant indirect effects whereby the competence need mediated associations between the social environment of coaching and athletes' vitality, negative affect, and physical self‐concept (defined as skillfulness and performance). Findings support theoretical assumptions and highlight that athletes' perceptions of what coaches do, and how they relate, are important to their psychological needs satisfaction and optimal functioning.